Fluid/structure Interaction Numerical Study on the Mechanical Integrity of Water Dam Reservoir Banks - Ng F.C.; Azman A.; Abas A.; Zawawi M.H.; Ahmad Mazlan A.Z.; Zahari N.M.; Mohd Remy Rozainy Z. (Institute of Physics Publishing, 2023)
Dam reliability analysis is conducted to access the integrity of dam structure and thus to prevent dam failure. This paper presents the numerical reliability study of reservoir banks of water dam by the mean of fluid/structure interaction (FSI) simulation. Through FSI, the hydrostatics effect of the water in reservoir on the wall of dam was successfully simulated and identified. From the current numerical work, relatively stagnant water on the dam bank was observed, with the increasing water pressure along the water depth. Subsequently, localized high stress and deformation on the dam structure was successfully identified, and suitable countermeasures were being recommended. For the current investigated dam bank structure, the highest deformation and stress detected are respectively 1.185 mm and 3.12 MPa. Therefore, at present operating configuration, it is concluded the bank would not exhibit any failures. Published under licence by IOP Publishing Ltd.